China’s Doing Business Success : Drivers of Reforms and Opportunities for the Future - Piatkowski, Marcin; Solf, Sylvia; Wei, Wenting (World Bank, Washington, DC, 2020)
The objective of this working paper is to: (i) document China’s business environment reform experience over the past few years, (ii) analyze the reform measures and the institutional arrangements that enabled this success, (iii) identify the remaining opportunities for business environment reforms; and (iv) share lessons learned from China’s experience with other economies that also aspire to improve the business environment.